Pelatihan Landing Page Untuk Santri Kreatif Pada Pondok Pesantren Al Mansyuriyah - Tri Santoso; Sulistianto SW (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Information technology is developing very rapidly. The development of information technology began with advances in the field of computerization. This development is based on the increasingly widespread use of information technology. In addition, it is supported by the development of various types of technological equipment and supporting applications. This has led to a significant technological shift from analog to digital technology, known as digitalization. Through digitalization, production processes can be accelerated, marketing or sales areas expanded, customer service improved, time efficiency, and so on. In order to create a creative generation, the concept of the creative industry must be instilled in the younger generation who are still receiving education. This aims to ensure that this generation will be able to think creatively when entering society and can help or even create jobs for the surrounding community. One of the young generations with the potential to become a creative generation is the Al Mansyuriyah Islamic Boarding School. To develop a creative young generation in the era of information technology development and digitalization, the Al Mansyuriyah Islamic Boarding School experiences limited knowledge about information systems and technology. This is what motivated us to carry out this community service to provide a presentation on Landing Page Training material for Creative Students. This community service program aims to enable students to express their creative ideas and utilize them according to their desires. The goal of this service activity is to provide insight into creating and utilizing landing pages as a creative tool that will ultimately benefit them and others. The output of this activity is a press release in local media and an unaccredited national journal.